Verification of Kaplan turbine Cam curves realization accuracy at power plant - Džepčeski, Dane D; Bogdanović, Slobodan; Stanojčić, Vladimir; Mitrović, Radomir; Bojanić, Zoran; Njegovan, Vesna; Marinović, Dragan (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
Sustainability of approximately constant value of Kaplan turbine efficiency, for relatively large net head changes, is a result of turbine runner variable geometry. Dependence of runner blades position change on guide vane opening represents the turbine cam curve. The cam curve realization accuracy is of great importance for the efficient and proper exploitation of turbines and consequently complete units. Due to the reasons mentioned above, special attention has been given to the tests designed for cam curves verification. The goal of this paper is to provide the description of the methodology and the results of the tests performed in the process of Kaplan turbine cam curves verification